2020
DOI: 10.3390/ijms21218261
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the JAK2/STAT3 Pathway—Can We Compare It to the Two Faces of the God Janus?

Abstract: Muscle cachexia is one of the most critical unmet medical needs. Identifying the molecular background of cancer-induced muscle loss revealed a promising possibility of new therapeutic targets and new drug development. In this review, we will define the signal transducer and activator of transcription 3 (STAT3) protein’s role in the tumor formation process and summarize the role of STAT3 in skeletal muscle cachexia. Finally, we will discuss a vast therapeutic potential for the STAT3-inhibiting single-agent trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 106 publications
0
17
0
Order By: Relevance
“…We found that the Y705 and S727 sites of Stat3 were phosphorylated upon Zinc treatment, suggesting that zinc activates Stat3. Previous studies reported that the upstream kinases of S727‐Stat3 were mainly MAPKs, such as ERK, JNK, or P38 (Bode et al, 2012; Ryu et al, 2018; Wang et al, 2019), and the upstream kinase of Y705‐Stat3 was JAK2 (Ceyzériat et al, 2016; Jaśkiewicz et al, 2020). Our experiment showed that activation of ERK and JAK2 regulated the phosphorylation of S727 and Y705 of Stat3, respectively, in zinc‐activated astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the Y705 and S727 sites of Stat3 were phosphorylated upon Zinc treatment, suggesting that zinc activates Stat3. Previous studies reported that the upstream kinases of S727‐Stat3 were mainly MAPKs, such as ERK, JNK, or P38 (Bode et al, 2012; Ryu et al, 2018; Wang et al, 2019), and the upstream kinase of Y705‐Stat3 was JAK2 (Ceyzériat et al, 2016; Jaśkiewicz et al, 2020). Our experiment showed that activation of ERK and JAK2 regulated the phosphorylation of S727 and Y705 of Stat3, respectively, in zinc‐activated astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…JAK2 serves as a signaling hub that integrates extracellular signals from interleukin receptors and oncogenic receptor tyrosine kinases into STAT3, which phosphorylates STAT3 at Y705 and homodimerizes with p-STAT3 to induce its nuclear translocation and transcriptional activity through interaction with its phosphorylated Y705 site and SH2 domain ( 53 , 54 ). STAT3 binds to the promoters of its target genes to induce tumor cell migration, growth, and differentiation and plays an important role in the development of a variety of tumors ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…JAK2/STAT3 pathway is a signal transducer and activator in tumorigenesis and development. 29 The anti‐cancer function of GL63 in HCC was also achieved by inactivating the JAK2/STAT3 pathway. 7 However, it remains unclear about the regulatory mechanism of GL63 in the JAK2/STAT3 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%